Ultrastructure of internal jugular vein defective valves. (October 2015) - Zamboni, P; Tisato, V; Menegatti, E; Mascoli, F; Gianesini, S; Salvi, F; Secchiero, P
Objectives: To study the ultrastructure of intraluminal defects found in the internal jugular vein by using a scanning electron microscopy. Methods: Using a scanning electron microscopy, intraluminal septa and/or defective valves blocking the flow in the distal internal jugular vein of seven patients were studied together with the adjacent wall and compared with control specimen. Results: The internal jugular veins' wall showed a significant derangement of the endothelial layer as compared to controls. Surprisingly, no endothelial cells were found in the defective cusps, and the surface of the structure is covered by a fibro-reticular lamina. Conclusions: Although the lack of endothelial cells in the internal jugular vein intraluminal obstacles is a further abnormality found in course of chronic cerebrospinal venous insufficiency, our investigation cannot clarify whether this finding is primary or caused by progressive loss of endothelium in relation to altered haemodynamic forces and/or to a past post-thrombotic/inflammatory remodelling.